Diffuse Interstellar Bands λ6379, λ6614, and λ6660 in the LAMOST-MRS Spectra. (1st August 2022) - Wu, Ke-Fei; Luo, A-Li; Chen, Jian-Jun; Hou, Wen; Zhao, Yong-Heng
Abstract: Diffuse interstellar bands (DIBs) have always been a mysterious existence in astronomical research. In this work, we provide more DIB samples to slightly uncover this mystery. With the LAMOST medium-resolution survey (MRS) spectra, we detected three DIBs λ 6379, λ 6614, and λ 6660, obviously superimposed on the spectra of 11, 003 stars. These spectra cover spectral types from O to K, which can provide a large number of candidates for further research on DIBs. The sample shows a clear positive correlation between the strength of DIBs and extinction, which agrees with the result in the literature. In addition, there exist two peaks in each of the velocity distribution of these three DIBs, and the velocity differences between two peaks of each pair are consistent. The reason for the two velocity components is due to the Galactic rotation.